Slowing gait during turning: how volition of modifying walking speed affects the gait pattern in healthy adults - Madrid, Julian; Benning, Leo; Selig, Mischa; Ulrich, Baptiste; Jolles, Brigitte M.; Favre, Julien; Benninger, David H. (Frontiers in Human Neuroscience, 2024)
Background Turning during walking and volitionally modulating walking speed introduces complexity to gait and has been minimally explored. Research question How do the spatiotemporal parameters vary between young adults walking at a normal speed and a slower speed while making 90°, 180°, and 360° turns? Methods In a laboratory setting, the spatiotemporal parameters of 10 young adults were documented as they made turns at 90°, 180°, and 360°. A generalized linear model was utilized to determine the effect of both walking speed and turning amplitude. Results Young adults volitionally reducing their walking speed while turning at different turning amplitudes significantly decreased their cadence and spatial parameters while increasing their temporal parameters. In conditions of slower movement, the variability of certain spatial parameters decreased, while the variability of some temporal parameters increased. Significance This research broadens the understanding of turning biomechanics in relation to volitionally reducing walking speed. Cadence might be a pace gait constant synchronizing the rhythmic integration of several inputs to coordinate an ordered gait pattern output. Volition might up-regulate or down-regulate this pace gait constant (i.e., cadence) which creates the feeling of modulating walking speed.